TARI CUNGKA : PERSPEKTIF MASYARAKAT BURANGASI KECAMATAN LAPANDEWA (STUDI KAJIAN SOSIOLOGYS HYSTORICAL) - Mansyur, Munawir (Jurnal Pendidikan Sejarah, 2024)
The problems in this research are: 1) What is the background to the emergence of the Cungka dance in Burangasi, Lapandewa District, South Buton Regency; 2) What values ​​are contained in the story regarding the background of the Cungka dance; 3) How does the Cungka dance move among the Burangasi community, Lapandewa District, South Buton Regency; 4) What values ​​are contained in the Cungka dance in Burangasi, Lapandewa District, South Buton Regency. The aims of this research are: 1) to find out the background to the emergence of the Cungka dance in Burangasi, Lapandewa District, South Buton Regency; 2) to find out the values ​​contained in the story regarding the background of the Cungka dance; 3) to find out the Cungka dance movements of the Burangasi community, Lapandewa District, South Buton Regency. 4) to find out the values ​​attached to the cungka dance. The research used in this research is descriptive qualitative with a historical approach. The data sources in this research are primary data sources and secondary data sources. Data collection techniques are interviews, observation and document study. The results of the research obtained are 1) The background to the emergence of the Cungka Dance from a husband and wife who bought 1 of their 7 children whose body parts were planted in the garden and grew into food in the form of heads becoming coconuts, teeth becoming corn, fingers and toes becoming cassava, blood becoming santa (tubers), and other body parts becoming hopa, peanuts, pumpkins and so on. 2) The value contained in the Cungka dance story is the value of obedience which the child (Wa Sariati) was willing to slaughter for the sake of the survival of her family. 3) the cungka dance moves turning right and left and swinging the arms and changing patterns like the letter (V) accompanied by the waironi song. 4) The value contained in the Cungka dance is the value of the beauty of every movement danced